Sound music and healing - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Human beings have been tantalized by sound and music since the beginning of civilization. Why does it seem that certain sounds soothe and comfort and invite us to reflect and other sounds seem to make us feel on edge, jittery, even anxious? Many people find themselves drawn to the sounds of the natural world, but why do these sounds resonate so deeply within us? And is there such a thing as sacred sound and music? What is happening to us now in modern life when we are bombarded by sound and noise at every turn? How is this new world of ceaseless sound affecting our bodies and our minds? This program explores some fascinating perspectives on our relationship with sound and music.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Music therapy; Music -- Psychological aspects; Holistic medicine; Sound